2010
DOI: 10.1111/j.1600-0684.2010.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Hematological, biochemical, respiratory, cardiovascular and electroneurophysiological parameters in African green monkeys (Cercopithecus aethiops sabaeus). Its use in non‐clinical toxicological studies

Abstract: We conclude that this study provides valuable integrated data for determining the health status, including electroneurophysiological parameters, data not previously reported for this species, of the African green monkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…The PLT values showed similar behavior to those reported by Kagira et al , which have been also presumed by the high coagulation requirements related with menstruation cycle. However, the ALT and AST values described in this study were lower than those reported in other previous studies , where the same specie was used. It may probably be explained by different animal dietary and maintenance conditions.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…The PLT values showed similar behavior to those reported by Kagira et al , which have been also presumed by the high coagulation requirements related with menstruation cycle. However, the ALT and AST values described in this study were lower than those reported in other previous studies , where the same specie was used. It may probably be explained by different animal dietary and maintenance conditions.…”
Section: Discussioncontrasting
confidence: 90%
“…For this reason, this study sought measuring and correlating the hematological and serum biochemical parameters of 400 captive housed African green monkeys grouped by sex and ages; including juvenile and adult animals, which was also a novel aspect in regard to previous available studies that used this species and others .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hematological parameters such as hemoglobin (Hb), platelets count, packed cell volume (PCV), white blood cell (WBC) count, and red blood cell (RBC) count were determined using an automated cell counter micros ABX (Roche Diagnostic System, Montpellier, France). 18…”
Section: Hematological Investigationmentioning
confidence: 99%